Sequence and function based screening of the goat rumen metagenome for novel amylases - Rabapane, Kgodiso Judith (Vaal University of Technology, 2019)
During one of our preliminary studies in 2015, metagenomic DNA extracted from the goat rumen was sequenced and the in silico mining of the biorefining enzyme showed the presence of significant number of different biocatalysts, such as amylases (E.C 3.2.1.1), xylanases (E.C 3.2.1.8), pectinases (E.C 3.2.1.15) and cellulases (E.C 3.2.1.4). Hence, a subsequent study was conducted which is aimed at extracting metagenomic DNA from the goat rumen, constructing the metagenomic library using pCC2-FOS™ plasmid vector (Epicentre®), and eventually screening the constructed library for potential novel amylases using soluble starch as a substrate. Accordingly, rumen digesta was aseptically collected from four compartments of each goat and pulled before extraction of metagenomic DNA. The conventional CTAB protocol was modified to extract the metagenomic DNA from the rumen digesta. As a result, high molecular weight DNA was obtained and used to construct the metagenomic fosmid library. Since the host (Escherichia coli EPI 300-T1r) supplied with CopyControlHTP Fosmid Library Production Kit has background amylase expression we opted for a knockout E. coli strain with deleted starch hydrolysis (amylase expression) pathway. The library was subsequently screened for the presence of amylase isoforms using soluble starch as a substrate. Therefore, for the purpose of this study, four fosmids clones showing amylase activity were selected, recombinant vector isolated and MiSeq-sequenced. Out of four recombinant proteins, only one (pET30a(+)-amy-vut12) was successfully expressed. Subsequently, pET30a(+)-amyvut12 was further characterize physicochemically. Interestingly, the recombinant enzyme showed maximum activity in the pH and temperature ranges of 6.0 - 8.0 and 70 - 90oC, respectively. Hence, this implies that novel recombinant protein has sound activity from acidic to alkaline pH range and potently thermostable. Further work should be done to optimize and improve the solubility of three other recombinant proteins (pET30a(+)-amy-vut2, pET30a(+)-amy-vut9 and pET30a(+)-amy-vut14) studied, which might harbour important traits. Most importantly, immobilization as well as crystallographic studies of pET30a(+)-amy-vut12 and downstream applications should further be investigated.
M. Tech. (Department of Biotechnology, Faculty of Applied and Computer Sciences), Vaal University of Technology.
Keywords: Starch; Metagenomics; Rumen; Amylases; Dissertations, Academic -- South Africa.; Metagenomics.; Biotechnology.; Starch.; Enzymes.; Amylases.